PESTEL's Holistic Framework for Rural Development - Ahmad, Hartini (2020)
Political, Economic, Socio-demographic (including Education), Technological, Environment, and Legislative (PESTEL) is the tool analysis to understand the current status and future needs of the external environment factors that people have. The PESTEL analysis is a strategic planning technique that provides a useful framework for analyzing the environmental pressures on rural people. The PESTEL aspects generating considerable interest in terms of the nature of it in a certain context of the study. There is limited knowledge of the holistic nature of PESTEL on the rural community and regional development in Malaysia. It is observed that there is limited support on certain PESTEL aspects that is important for some people based on different demographic profiles such as gender, age, income, occupation, etc. What people have and what aspects they want to have more. The outcomes of this study would contribute to the policymaker, such as the Ministry of Rural and Regional Development (MRRD), and raise the attention at the national as well as the international levels, particularly in the change management era in Malaysia and Indonesia. Particularly in the Covid-19 pandemic faced by the world recently